2011
DOI: 10.4103/2152-7806.90689
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid rhinorrhea: An institutional perspective from Pakistan

Abstract: Background:The management of cerebrospinal fluid (CSF) rhinorrhea has evolved over the last two decades. We present here a review of our 11-year data on CSF rhinorrhea and its management at a tertiary care hospital in a developing country, with particular reference to the diagnosis, surgical management and outcome of the disease.Methods:The medical charts of all patients with a diagnosis of CSF rhinorrhea over an 11-year period were reviewed. The etiology of CSF rhinorrhea was classified into three categories:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 16 publications
2
12
0
2
Order By: Relevance
“…Endoscopic technique offers reduced postoperative morbidity and reduced length of hospitalization (usually 48 hours), which were confirmed in our case, and avoids the complications of craniotomy, such as anosmia and intense headaches [8]. Endoscopic technique can be applied to either small or large defects [5].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Endoscopic technique offers reduced postoperative morbidity and reduced length of hospitalization (usually 48 hours), which were confirmed in our case, and avoids the complications of craniotomy, such as anosmia and intense headaches [8]. Endoscopic technique can be applied to either small or large defects [5].…”
Section: Discussionsupporting
confidence: 75%
“…The average calculated risk of recurrence of CSF leak is 21%, with the complication rate increasing with increased duration of uncorrected leak [5]. A second attempt in case of relapse has a success rate of 97%, underlining that a prior failed surgical treatment of defect is not an indication to proceed with diversion or conservative treatments [7][8][9]. In our case, the patient was subjected to lumbar diversion twice following failed surgical treatment, resulting in recurrent episodes of meningitis and being exposed to a risk of permanent neurological damage and death each time.…”
Section: Discussionmentioning
confidence: 99%
“…If the leak does not respond to conservative measures in two weeks, then it is imperative to intervene invasively. [5][6][7] The common investigations performed to detect skull fracture and hence the suspected dural tear area by the high-resolution CT scan is seen with coronal and sagittal cuts. MRI with T2 weighted images in prone position is also highly favored.…”
Section: Original Articlementioning
confidence: 99%
“…Beta transferrin of the leaking fluid and its glucose levels are also helpful in differentiation between CSF rhinorrhea from other causes. [7][8][9] Complications of posttraumatic CSF leaks include acute fulminant meningitis with a considerably higher mortality rate, repeated pneumocephalus with the possibility of tension pneumocephalus. [9][10][11][12] Bell et al 13 has conducted a review of posttraumatic CSF leaks and its management and has reported that these leaks are present in 4.6% of head trauma patients.…”
Section: Original Articlementioning
confidence: 99%
“…При написании литературного обзора мы проанализировали 7 статей, подходивших под критерии включения. Во всех исследованиях [29][30][31][32][33][34][35] Следует отметить, что в норме на КТВР могут определяться подозрительные на наличие дефекта участки основания черепа, но не все дефекты являются источниками ликвореи. Из-за недостатка специфичности, в некоторых исследованиях рекомендуется использовать комбинацию КТ и МРТ [36].…”
Section: результатыunclassified